Extravascular lung water and sepsis [Damar dişi akciǧer suyu ve sepsis] - (:unkn) unknown (My University, 2013)
The incidence of sepsis has been increasing because of the advancing age of the general population, a greater number of invasive procedures, and more immunosuppressive therapies. Nowadays, the mortality of sepsis is still high, and is still the major cause of morbidity and mortality for patients admitted to an intensive care unit. In sepsis, exaggerated responses might induce organ dysfunction including lung injury and shock, whether the focus is located in the lung or not. Extravascular lung water (EVLW) consists nearly of fluid in the pulmonary interstitial and alveolar spaces. EVLW can be measured at the bedside using the transpulmonary thermodilution technique and has a diagnostic value for the identification of patients. It is an indicator of prognosis and severity of sepsis-induced lung injury. Measurement of EVLW is useful in characterising the severity of respiratory disease, it is also beneficial in the management of patients with sepsis. Increased EVLW is associated with decreased life expectancy in patients with sepsis. Reduction of EVLW at an early stage and a negative fluid balance are associated with a more favorable outcomes. Key words as sepsis, septic shock, lung injury and extravascular lung water are searched in various databases and the prognostic, diagnostic and clinical significance of EVLW in sepsis and sepsis induced lung injury are discussed in this review.
Keywords: Extravascular lung water; Lung injury; Sepsis; Transpulmonary thermodilution